Valoration of the Synthetic Antioxidant Tris-(Diterbutyl-Phenol)-Phosphite (Irgafos P-168) from Industrial Wastewater and Application in Polypropylene Matrices to Minimize Its Thermal Degradation (2023)
Industrial wastewater from petrochemical processes is an essential source of the synthetic phenolic phosphite antioxidant (Irgafos P-168), which negatively affects the environment. For the determination and analysis of Irgafos P-168, DSC, HPLC-MS, and FTIR methodologies were used. Solid phase extraction (SPE) proved to be the best technique for extracting Irgafos from wastewater. HPLC-MS and SPE determined the repeatability, reproducibility, and linearity of the method and the SPE of the standards and samples. The relative standard deviations, errors, and correlation coefficients for the repeatability and reproducibility of the calibration curves were less than 4.4% and 4.2% and greater than 0.99955, respectively. The analysis of variance (ANOVA), using the Fisher method with confidence in 95% of the data, did not reveal significant differences between the mentioned parameters. The removal of the antioxidant from the wastewater by SPE showed recovery percentages higher than 91.03%, and the chemical characterization of this antioxidant by FTIR spectroscopy, DSC, TGA, and MS showed it to be structurally the same as the Irgafos P-168 molecule. The recovered Irgafos was added to the polypropylene matrix, significantly improving its oxidation times. An OIT analysis, performed using DSC, showed that the recovered Irgafos-blended polypropylene (PP) demonstrated oxidative degradation at 8 min. With the addition of the Irgafos, the oxidation time was 13 min. This increases the polypropylene’s useful life and minimizes the environmental impact of the wastewater.